Case of successful treatment of disseminated pneumocystosis with lesions of lungs and small intestine in an HIV-infected patient - V. V. Svistunov; A. E. Makarova; V. A. Zinserling (Журнал инфектологии)
The paper describes a rare case of pneumocystosis of the small intestine, diagnosed in the surgical material of a 39-year-old man with HIV infection using histological and immunohistochemical methods. After the treatment, the patient was discharged.